The Role of Rasaja Bhava (Nourishing Factors) in Development of Garbha (Embryo/Foetus) (International Journal of Ayurveda and Pharma Research, 2023)
Archaic scholars of Ayurveda lay great emphasize on intake of Ahara (food) as best source for nourishment and has a prime role in growth and development of foetus during pregnancy. In order to achieve a healthy progeny, Ayurveda classics have elucidated wholesome regimen to be followed by the parents before and after conception. There are specific procreating factors which help for the growth of embryo known as Matrujadi shad bhava (maternal and other 5 factors). Shadbhava (six factors) consist of Matruja, pitruja, Atmaja, Rasaja, Satmyaja and Satwaja in which Rasaja bhava plays an important role in providing nutrition to the foetus. The concept of Upasneha, Upasweda, Ambu, Apara and Nabhinadi are involved in nourishment of embryo/foetus at different stages of development. Acharya have drawn attention to certain food habits, to be avoided by the pregnant woman to refrain from abnormalities in the offspring. The concept of nutrition in Garbhini (Gravid Women) explained in classics has similarity with contemporary science.